Research on Public Service Motivation and Leadership: A Bibliometric Study - Marques, Tânia M. G. (2020)
Using a bibliometric approach, this quantitative study collects and analyses 61 publications on Public Service Motivation and Leadership simultaneously, within the public administration field, published in Web of Knowledge/SSCI database until 2018. This article seeks to contribute to a better understanding of the topics by complementing conventional qualitative literature reviews. The results demonstrate that, recently, a continuous increase of the research has occurred, and the US is the country driving the research. Thus, other parts of the globe should be cautious when adopting the conclusions of studies from such a different cultural context. Moreover, the transformational leadership research emerge from the results. Nevertheless, other leadership approaches are welcome, such as responsible leadership. Based on the review, the article suggests directions for further research endeavors.